Prospects for economic integration of the South Caucasus countries with the European Union - Khatuna Berishvili (Scientific Results, 2025)
The European Union's Eastern Partnership (EaP) program is one of the key instruments of its foreign policy for relations with six post-Soviet countries in Eastern Europe and the South Caucasus.These countries are: Georgia, Ukraine, Azerbaijan, Belarus, Moldova, and Armenia. This initiative promotes cooperation between the European Union and the six participating countries, including Georgia, Azerbaijan, and others, in the fields of economics, politics, and trade. Research on the challenges and prospects of the Eastern Partnership has garnered significant attention from scholars. However, a more in-depth analysis of the dynamics of relations between the European Union and the participating countries of the Eastern Partnership, both bilaterally and multilaterally, is needed. This article aims to contribute to such research